(untitled) (MCIT: Proceedings of International scientific and practical conference, 2023)
This paper investigates the use of fuzzy numbers and the annealing method to find a solution to the traveling salesman problem, which involves finding the shortest time route for a given set of cities. Fuzzy numbers are used to model the inaccuracy and uncertainty of input data, and an annealing method is proposed to find solutions. A comparison of the results of the TSP problem using crisp and fuzzy numbers using the annealing method was carried out. The results of numerical experiments are given, which show that the use of fuzzy numbers, in particular triangular and parabolic, with the annealing method leads to a significant improvement in the results of the TSP problem compared to the use of crisp numbers. У цій статті досліджується використання нечітких чисел і методу відпалу для пошуку розв’язку проблеми комівояжера, яка передбачає пошук найкоротшого маршруту для даного набору міст. Для моделювання неточності та невизначеності вхідних даних використовуються нечіткі числа, а для пошуку рішень пропонується метод відпалу. Проведено порівняння результатів задачі TSP з використанням чітких і нечітких чисел за допомогою методу відпалу. Наведено результати чисельних експериментів, які показують, що використання нечітких чисел, зокрема трикутних і параболічних, з методом відпалу призводить до значного покращення результатів задачі TSP порівняно з використанням чітких чисел.